Agenesis of the Corpus Callosum Associated with Persistent Primitive Olfactory Artery - Case Report and Literature Review - Myoung Soo Kim (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Agenesis of the corpus callosum (ACC) is a congenital malformation that can occur in isolation or  in  associatio with other neurological conditions.However, to our knowledge,no cases of ACC associated with persistent primitive olfactory artery (POA) have been reported. Here we report a case involving a patient with ACC associated with persistent POA.A 57-year-old man was admitted to our hospital because of trauma to his face.Neurological findings were normal.Face computed tomography (CT) showed a mandible fracture.Brain CT and magnetic resonance imaging (MRI) demonstrated total ACC, intact anterior commissure, and no development of hippocampal commissure. CT angiography of the brain demonstrated a right persistent POA. The findings in this case suggest that CT angiography or MRI may detect persistent POA more effectively in cases involving ACC.